Islamic Fintech as a Catalyst for Digital Economic Transformation: Opportunities, Challenges, and Policy Strategies in Indonesia - Andi Setyo Pambudi (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2026)
Digital transformation has significantly reshaped the Islamic economic landscape through the adoption of financial technology (fintech), which offers faster, more efficient, and inclusive financial services. As the country with the world's largest Muslim population, Indonesia possesses substantial potential to leverage Islamic fintech in supporting Islamic economic development through expanded financial access, enhanced financing for micro, small, and medium enterprises (MSMEs), the growth of Sharia-compliant investments, and the optimization of digital zakat and waqf management. Nevertheless, the development of Islamic fintech continues to face several challenges, including low levels of Islamic financial and digital literacy, limited human resource capacity, cybersecurity risks, capital constraints, and the need for regulatory harmonization. This study aims to analyze the transformation of the Islamic economy in the digital era, identify the opportunities offered by Islamic fintech, examine the challenges it encounters, and formulate strategies for its sustainable development. The study employs a descriptive qualitative approach through a literature review, utilizing content analysis and SWOT analysis of scientific publications and policy documents. The findings indicate that Islamic fintech plays a strategic role in enhancing financial inclusion, strengthening the halal ecosystem, and supporting inclusive economic development. Therefore, strengthening regulations, improving public literacy, developing human resources, enhancing digital security, and integrating the halal ecosystem are essential to improving the long-term competitiveness of Islamic fintech.